2022
DOI: 10.18502/ijph.v51i2.8681
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Fortified Products on Bone Bi-omarkers: A Systematic Review and Meta-Analysis

Abstract: Background: Vitamin D plays an essential role in the regulation of bone metabolism. The current meta-analysis aimed to assess the effectiveness of vitamin D fortification on special bone biomarkers. Methods: Five main databases (PubMed/Medline, ISI Web of Knowledge, Science Direct, Scopus, Cochrane Library as well as Science Direct, and Scopus) were considered for this systematic review, until Jan 2020. All randomized controlled trials were included to evaluate the probable relationship between consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…The systematic reviews included 2 to 40 vitamin D fortification trials. Of the 27 systematic reviews, 5 included children only [44,[56][57][58]60], and 7 included exclusively adults [36,42,43,[46][47][48]59], while in 15 reviews all age groups were included [35,[37][38][39][40][41]45,[49][50][51][52][53][54][55]61]. Most of the systematic reviews included studies of both sexes, with the exception of two studies including only women [48,53].…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic reviews included 2 to 40 vitamin D fortification trials. Of the 27 systematic reviews, 5 included children only [44,[56][57][58]60], and 7 included exclusively adults [36,42,43,[46][47][48]59], while in 15 reviews all age groups were included [35,[37][38][39][40][41]45,[49][50][51][52][53][54][55]61]. Most of the systematic reviews included studies of both sexes, with the exception of two studies including only women [48,53].…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
“…While most of the studies did not apply restrictions based on the geographic location of the study [35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], one systematic review included only RCTs from Iran [43]. Only eight systematic reviews reported data on other forms of vitamin D intake, e.g., from sun exposure or dietary vitamin D intake from other foods or supplements [35,36,38,40,41,52,58,59].…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis conducted in 2017 on twenty randomised clinical trials (RCT) showed that consumption of vitamin-fortified foods can significantly increase serum 25(OH)D and bone mineral density levels and decrease PTH concentrations, without having a beneficial effect on bone turnover markers (12) . In another meta-analysis of forty RCT in 2020, vitamin D fortification resulted in significant reductions in serum levels of PTH and C-terminal telopeptide of type-I collagen (CTX), with no impact on bone mineral density (13) . These two meta-analyses evaluated the effect of vitamin D fortification on bone markers regardless of biological differences in the two sexes.…”
mentioning
confidence: 99%